Cryogenic amplifiers for interfacing superconductive systems to room temperature electronics - Badenhorst, Le Roux (Stellenbosch : Stellenbosch University, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--Stellenbosch University, 2008.